A colorimetric/SERS dual-mode sensing method for the detection of mercury(ii) based on rhodanine-stabilized gold nanobipyramids. Issue 45 (2nd November 2018) - Qi, Ying; Zhao, Jing; Weng, Guo-jun; Li, Jian-jun; Li, Xin; Zhu, Jian; Zhao, Jun-wu
Abstract : This study demonstrates a novel strategy for colorimetric and surface enhanced Raman scattering (SERS) dual-mode sensing of mercury (Hg 2+ ) based on rhodanine-stabilized gold nanobipyramids (Au NBs). Abstract : This study demonstrates a novel strategy for colorimetric and surface enhanced Raman scattering (SERS) dual-mode sensing of mercury (Hg 2+ ) based on rhodanine-stabilized gold nanobipyramids (Au NBs). The Au NBs are first modified by rhodanine through gold–thiol (Au–S) affinity interactions. Next, the addition of Hg 2+ into the rhodanine-stabilized Au NBs induces the formation of a partition layer with tunable thickness on the surface of the Au NBs, resulting in the redshift of the longitudinal localized surface plasmonic resonance (LSPR) wavelength of the Au NBs, which further leads to the colloidal color changing from blue grey to red. The sensing based on the partition layer-induced absorption spectrum redshift of the longitudinal LSPR has a linear response for the concentration of Hg 2+ from 5.0 × 10 −7 to 6.0 × 10 −5 M with a limit of detection (LOD) of 2.0 × 10 −7 M measured by an absorption spectrometer. The LOD for Hg 2+ is 2.0 × 10 −6 M by the naked eye. Meanwhile, the partition layer on the surface of the Au NBs draws the Raman reporter molecule (4-mercaptobenzoic acid (4-MBA)) away from the surface of the Au NBs and decreases the LSPR phenomenon of the Au NBs, which leads to the SERS intensity of 4-MBA decreasing with the addition of Hg 2+ . The sensing based on the partition layer-induced SERS intensity decrease of 4-MBA has a linear response for the logarithm of Hg 2+ concentration from 1.0 × 10 −10 to 1.0 × 10 −5 M with a LOD of 5.0 × 10 −11 M. Therefore, the rhodanine-stabilized Au NBs can be used not only as a naked-eye sensor of Hg 2+, but also as a highly selective SERS probe. Furthermore, other cations do not interfere with this dual-mode sensor, and the applicability of the sensor is well demonstrated in real samples with satisfactory results. Compared with the methods in the literature, which generally exploit the aggregation or etching of nanoparticles, this method depends on the formation of a partition layer on the surface of the nanoparticles and provides a new strategy for optical sensing that relies on the change in dielectric environment near the surface of the nanoparticles.